Analysis of the Implementation of Clean and Healthy Lifestyle Development Program School Order - Kodrat Pramudho; Dian Utama Pratiwi Putri; Yessiana Luthfia Bahri (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2021)
Clean and Healthy Behavior in school is a positive behavior carried out by every student, teacher, school guard, canteen officer or school stall, parents of students to prevent illness, improve their health and be active in maintaining a healthy environment at school independently. The purpose of the study was to know in depth the Implementation of School Order Development Program PHBS in elementary students in East Lampung District in 2020. The type of this research is qualitative and the results of the study are presented in a descriptive form. Subjects or informants were taken by Purposive Sampling. The number of informants was 14 people. Data collection techniques employed in-depth interviews and observation techniques. Data analysis was carried out by organizing the data obtained into a category, describing the data into units, analyzing important data, compiling or presenting data in accordance with the research problem in the form of conclusions that are easy to understand. Based on in-depth interviews with 14 informants there were 3 factors that influenced the success of the PHBS program in schools, namely input indicators (policy, support, funding, human resources, facilities and infrastructure, and institutions), Process indicators (Advocacy, cadre training, socialization, plans activities, implementation movements, monitoring) and output indicators (8 indicators of Clean and Healthy Behavior in school). Furthermore, it can be summed up that Cross Programs and Cross Sectors are very influential in the successful implementation of Clean Life and Seat behavior programs in Schools by taking into account Input Indicators, Pross Indicators and Output Indicators